Effect of serrated grain boundary on stress corrosion cracking of Alloy 600 - Kim, H.P.; Choi, M.J.; Kim, S.W.; Kim, D.J.; Lim, Y.S.; Hwang, S.S. (Nuclear engineering and technology, 2018)
The effect of a serrated grain boundary on stress corrosion cracking (SCC) of Alloy 600 was investigated in terms of improvement of SCC resistance. Serrated grain boundaries and straight grain boundaries were obtained by controlled heat treatment. SCC cracks preferentially initiated and grew at grain boundaries normal to the tensile loading axis. Resolved tensile stress normal to the grain boundary was lower in serrated grain boundaries compared to straight grain boundaries. The specimen with serrated grain boundaries showed higher SCC resistance than that with straight grain boundaries due to a lower resolved tensile stress normal to the grain boundary. Keywords: Alloy 600, Stress corrosion cracking, Serrated grain boundary, Tensile stress, NaOH